الوظفية الفنية والسمات الجمالية للاكسسوارات فى العمل السينمائى المعهد العالي لتقنيات الفنون/طرابلس (Al-Farooq Journal of Sciences, 2026)
This research examines the artistic function and aesthetic features of accessories in cinematic works as an active visual element within the frame, not merely a supplementary component. The research stems from a problem related to the weak awareness of the function of accessories in some works, where they are sometimes used in a purely formal way that does not contribute to building dramatic meaning. The research aims to analyze the role of accessories in shaping visual meaning, revealing their relationship to the character and the narrative, in addition to clarifying the extent of their influence on directing the viewer's perception and forming the perceived image. The research adopted the descriptive analytical method by studying accessories within the system of cinematic composition, linking them to elements such as costumes, lighting, camera movement, and editing. The semiotic perspective was also employed in analyzing accessories as a visual sign carrying multiple levels of meaning, starting from direct meaning and extending to symbolism and suggestion. The study demonstrated that props can play a pivotal role in character development, revealing psychological and social dimensions, and can even become independent iconic elements contributing to meaning within the work. The findings also revealed that the significance of props is inseparable from the dramatic context, shaped by their relationship to other visual elements and by the viewer's perception of them both within and outside the frame. The study confirmed that the conscious use of props enhances the power of the cinematic image and contributes to visual cohesion, while their careless use weakens the artistic impact.
Keywords: Cinematic props, visual significance, perceived image, cinematic composition